Analisis Kualitas Batubara pada Sumur Bor AR_10 di Kabupaten Muaraenim, Sumatera Selatan - Ridho Rizky Amanda (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the quality of coal from the AR_10 borehole in Muara Enim Regency, South Sumatra, based on proximate analysis. The AR_10 borehole has three coal seams (A, B, and C) that were analyzed using the standard ASTM method to determine the coal quality characteristics. The parameters analyzed include total moisture (TM), volatile matter (VM), fixed carbon (FC), ash content (Ash), calorific value (CV), and total sulfur (TS) on an as-received (AR) basis. The analysis results show that seam A has the highest moisture content (19%), seam B exhibits the optimal calorific value (6045 kcal/kg), and seam C has the highest fixed carbon content (42.63%) with the highest sulfur content (0.83%). The correlation between parameters indicates that increases in moisture and ash content negatively affect the calorific value, while an increase in fixed carbon is positively correlated with the calorific value. All three seams fall into the category of low to medium rank coal (subbituminous to high volatile bituminous) with adequate quality for power generation and industrial purposes. This research provides an important contribution to the characterization of Muara Enim Formation coal in South Sumatra for the optimization of local coal resource utilization.